The Influence of Environmental, Social, and Governance Disclosure and Carbon Emission Disclosure on the Financial Performance of Mining Companies on the Indonesia Stock Exchange - Keisha Rana Deandra; Patria Prasetio Adi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The mining industry in Indonesia continues to encounter challenges in maintaining capital structure stability amid the increasing demand for sustainability disclosure. This study examines the effect of Environmental, Social, and Governance Disclosure together with Carbon Emission Disclosure on Financial Performance in mining companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The study was conducted due to the inconsistent findings reported in previous research. A quantitative approach was applied using purposive sampling, resulting in 21 selected companies out of 41 companies with a total of 105 observations. The data analysis employed multiple linear regression using IBM SPSS Statistics 27. The findings show that, partially, environmental disclosure and social disclosure have a negative but insignificant relationship with financial performance. Meanwhile, governance disclosure and carbon emission disclosure demonstrate a positive yet insignificant relationship with financial performance. Simultaneously, ESG disclosure and carbon emission disclosure were also found to have no significant influence on the financial performance of mining companies. These findings suggest that sustainability disclosure practices within the Indonesian mining sector are still mainly implemented to comply with regulatory requirements rather than functioning as a key factor influencing corporate capital structure.